2007
DOI: 10.1007/bf03166256
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field dependence of13C photo-CIDNP MAS NMR in plant photosystems I and II

Abstract: Photochemically induced dynamic nuclear polarization is observed in the two photosynthetic reaction centers of plants, photosystem I (PSI) and photosystem II (PSII) by ~~C magic-angle spinning nuclear magnetic resonance (NMR) at three different magnetic fields 17.6, 9.4, and 4.7 T, There is a significant difference in field dependence detected in the light-induced signal pattern of the two photosystems. For PSII the optimal NMR. enhancement factor of about 5000 is observed at 4.7 T. On the other hand, the maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
(44 reference statements)
3
19
0
Order By: Relevance
“…5b) at different magnetic field strengths. In line with previous observations in spinach PSI [31], the light-induced signals of duckweed PSI increase in intensity with an increasing magnetic field strength from 2.4 T up to 9.4 T. Within the limited range of the observed fields, the field dependence of the solid-state photo-CIDNP effect in duckweed seems to be similar to that in spinach (Fig. 5).…”
Section: The Magnetic Field Effect Of Photo-cidnp In Different Plant Psisupporting
confidence: 91%
See 2 more Smart Citations
“…5b) at different magnetic field strengths. In line with previous observations in spinach PSI [31], the light-induced signals of duckweed PSI increase in intensity with an increasing magnetic field strength from 2.4 T up to 9.4 T. Within the limited range of the observed fields, the field dependence of the solid-state photo-CIDNP effect in duckweed seems to be similar to that in spinach (Fig. 5).…”
Section: The Magnetic Field Effect Of Photo-cidnp In Different Plant Psisupporting
confidence: 91%
“…The field dependence of the solid-state photo-CIDNP effect in PSI from spinach has been measured previously [31] and it was shown that the effect decays at high fields having a maximum at about 9.4 T. Figure 5 shows the relative signal-to-noise intensity of the photo-CIDNP signals obtained from uniformly 15 N-labeled PSI of duckweed (Fig. 5a) and spinach (Fig.…”
Section: The Magnetic Field Effect Of Photo-cidnp In Different Plant Psimentioning
confidence: 68%
See 1 more Smart Citation
“…[19] From both phyla, no experiments with photo-CIDNP MAS NMR have been reported so far. The effect is not limited to bacterial RCs but is also observed in RCs of plants, e.g., Spinacia oleracea [20] [21] [22] and Spirodella oligorrhiza. [23] Furthermore, it was demonstrated, that photo-CIDNP can also be observed in the C57S-mutant of phototropin LOV1 [24] from the green alga Chlamydomonas rheinhardtii.…”
Section: Introductionmentioning
confidence: 93%
“…[61][62] Also entirely emissive spectra have been observed on PS I particles of Spinacia oleracea (spinach). [20] In contrast, RCs of R. sphaeroides R26 [9][62] and PS II (D1/D2 preparation) of spinach [22] show enhanced absorptive signals of the aromatic carbons together with the emissively polarized methine carbons. In these samples, due to the absence of carotenes in the vicinity of the donor, long donor triplet lifetimes, and therefore the DR mechanism can occur.…”
Section: Mas-nmr Measurementsmentioning
confidence: 99%